KESALAHAN SISWA MENYELESAIKAN SOAL CERITA MATEMATIKA BERDASARKAN SKEMA FONG: SYSTEMATIC LITERATURE REVIEW - M Akbar Gulvara; Didi Suryadi; Surya Kurniawan (IKIP Siliwangi, 2023)
This study aims to conduct a literature review on student error analysis in solving mathematical word problems using the Fong schema model across all levels of education. The study utilized the SLR (Systematic Literature Review) method to collect data by identifying and examining all relevant articles published between 2013 and 2023. A search of the Google Scholar database using Harzing's Publish or Perish application yielded 21 articles that met the review theme criteria. The results of this research reveal fluctuations in the number of studies conducted over the past ten years. Based on the research criteria, most studies were conducted on junior high school students, particularly on the topic of solid geometry, with the majority of research subjects coming from Java Island. Common student errors found include procedural mistakes and incomplete conclusions, which are essential to consider in mathematics learning.